2021
DOI: 10.1002/jgh3.12682
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to hepatocellular carcinoma in chromosome 22q13.31, findings of a genome‐wide association study

Abstract: Background and Aim: Chronic hepatitis C virus (HCV) infection, long-term alcohol use, cigarette smoking, and obesity are the major risk factors for hepatocellular carcinoma (HCC) in the United States, but the disease risk varies substantially among individuals with these factors, suggesting host susceptibility to and gene-environment interactions in HCC. To address genetic susceptibility to HCC, we conducted a genome-wide association study (GWAS). Methods: Two case-control studies on HCC were conducted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…GG carriers were found to evince a 5-fold increased risk compared to CC carriers[ 51 ]. This association was confirmed by subsequent studies[ 52 , 53 ]. The TM6SF2 rs58542926 polymorphism has been reported to be another risk factor for HCC and advanced fibrosis/cirrhosis[ 54 , 55 ].…”
Section: Genetic Risk Factorssupporting
confidence: 79%
“…GG carriers were found to evince a 5-fold increased risk compared to CC carriers[ 51 ]. This association was confirmed by subsequent studies[ 52 , 53 ]. The TM6SF2 rs58542926 polymorphism has been reported to be another risk factor for HCC and advanced fibrosis/cirrhosis[ 54 , 55 ].…”
Section: Genetic Risk Factorssupporting
confidence: 79%
“…We also explored the association of rs3747207, rs4823173 and rs2896019 with HCC susceptibility. One study has also revealed the significant correlation of PNPLA3 rs4823173 and rs2896019 with HCC susceptibility [ 24 ]. Notably, although no association was observed between the alleles and genotypes of rs4823173 and HCC susceptibility, our study demonstrated that the rs2896019 G allele and GG genotype were obviously associated with increased HCC susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, a common variant in the toll-like receptor 5 , rs5744174, was linked to the development of HCC [ 28 ], while genetic variation in platelet receptors does not seem to play a role [ 29 ]. In the same line, we analysed two polymorphisms in SAMM50 because a recent genome-wide association study linked the genetic variation of SAMM50 to the development of HCC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that SAMM50 is upregulated in patients with NAFLD, that this upregulation is impaired in the presence of genetic variants in polymorphisms associated with NAFLD and that experimental knock-down of SAMM50 leads to intracellular triglyceride accumulation [ 18 ]. In line with changed expression, both rs3761472 and rs3827385 were reported to affect the binding of transcription factors and were linked to SAMM50 mRNA expression level in adipose tissue [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation